Frequency and Risk Factors Associated with Positive Cases of Hepatitis B and Hepatitis C in 100 Dialysis Dependent Patients - Riaz Gul; Ahmad Zeb; Naila Sher (Gandhara University, 2015)
The main objective of the study was to determine the frequency of hepatitis B and hepatitis C in hemodialysis dependent patients who are positive for either type of hepatitis infection. Methodology: Study was conducted for duration of five months (1st Dec 2014- 23rd April 2015) at nephrology unit of Khyber teaching hospital and kidney center of Hayat Abad medical complex. Patients who were dependent on dialysis with renal failure due to any cause were targeted for the study. All patients who were found positive for either type of hepatitis infection were included in the study. All patients who were positive with hepatitis infection before the start of dialysis and those who came for the first time for dialysis were excluded from the study.A semi structured questionnaire with both open and close ended questions was used to collect the information from the patients. Written consent was taken from all the patients prior to the data collection after explaining purpose of the study. It was a cross sectional study and non-probability convenient sampling technique was adopted for the data collection. Total of hundred patients who were positive for hepatitis were taken as sample size. Patient's record was also thoroughly checked as an adding tool for data collection. Apart from patients some inquiry was also done from the concerned staff working on dialysis machines. Results: Results of this study show that the prevalence of hepatitis infection is more in dialysis dependent patients as compared to the general population, and that among the positive cases the frequency of hepatitis C was more than hepatitis B. Common risk factors associated with increase prevalence of hepatitis infection among hemodialysis dependent patients are frequent blood transfusion without proper screening, lack of proper sterilization of dialysis machine and environment where dialysis is carried out. Close proximity of the patients with positive cases of hepatitis positive patients, previous surgical procedures carried out, history of hepatitis infection in family and decreased immunity of the dialysis patients Conclusions: Frequent dialysis leads to increase frequency of hepatitis C as compared to hepatitis B and unsterilized environment of the area around the machine and unscreened blood transfusion are the major contributors.